(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Selenium is an antioxidant that prevents oxygen radical from damaging cells from chronic diseases that can develop from cell injury and inflammation such as diabetes mellitus. The aim of the study is to investigate the possible protective effect of selenium yeast on cholesterol diet induced type-2 diabetes mellitus and oxidative stress in rats. Twenty male wistar rats were divided in to four groups of five animals each: Group 1: (Negative control) received standard animal feed only, Group 2: received cholesterol diet (CD) only, Group 3: received CD and 0.1 mg/kg selenium yeast orally, Group 4: Received CD and 0.2 mg/kg selenium yeast orally for six weeks. At the end of the study period, the animals were sacrificed and the serum samples were collected and evaluated for estimation of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx). The results showed a significant (P < 0.05) decrease in blood glucose level in the groups co-administered CD and selenium yeast when compared to CD group only. Antioxidant enzymes status recorded significant (P < 0.05) decrease in SOD, CAT and GPx activities in CD and selenium yeast administered when compared to CD group only. In Conclusion, Selenium yeast administrations prevent free radical formations which are potent inducer of diabetes mellitus.